2021
DOI: 10.1088/1757-899x/1197/1/012075
|View full text |Cite
|
Sign up to set email alerts
|

Status of Agro-Industrial Waste Used to Develop Construction Materials in Andhra Pradesh Region – India

Abstract: In today’s world concrete is one of the major construction materials. With the growth in industrialization and urbanization the demand for the concrete has taken a new pace. Therefore, to fulfill the demand huge amounts of natural resources has to be exploited for the production of the cement because natural resources and raw materials are major constituents in the production. At the same time huge quantities of industrial and agricultural wastes are generating in developing countries and are posing serious ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…The total wastes generated and cement manufactured globally per year are 2.01 billion and 4.1 billion tonnes, respectively, as shown in Fig. 2a, which would keep on increasing in the coming years [12][13][14]. Out of these wastes material, 44% of the contribution is from agricultural and food wastes, while remaining 56% contributes from industrial and other wastes, which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total wastes generated and cement manufactured globally per year are 2.01 billion and 4.1 billion tonnes, respectively, as shown in Fig. 2a, which would keep on increasing in the coming years [12][13][14]. Out of these wastes material, 44% of the contribution is from agricultural and food wastes, while remaining 56% contributes from industrial and other wastes, which is shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Out of these wastes material, 44% of the contribution is from agricultural and food wastes, while remaining 56% contributes from industrial and other wastes, which is shown in Fig. 2b [12,14]. According to "CemWeek research's 2020 update of the Global Ground Granulated Blast Furnace Slag Market Report and Forecast", total amount of GGBS production is about to reach 269 million tonnes between 2020 and 2025, while fly ash production which was 225 million tonnes in year 2020 would also drastically increase [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation